Individual Differences in the Neural Basis of Causal Inferencing - Prat, Chantel S. (2010)
This study used fMRI to examine individual differences in the neural basis of causal inferencing. Participants with varying language skill levels, as indexed by scores on the vocabulary portion of the Nelson-Denny Reading Test, read four types of two-sentence passages in which causal relatedness (moderate and distant) and presence or absence of explicit clause connectives were orthogonally varied to manipulate coherence and cohesion during inference generation. Skilled readers showed better neural efficiency (less activation) during all context sentences and during all inference conditions. Increased activation in less-skilled readers was most extensively distributed in the right hemisphere (RH) homologues of left hemisphere (LH) language areas, especially in the most difficult passage types. Skilled readers also showed greater sensitivity to coherence (greater activation and synchronization in moderately related than distantly related passages) whereas less-skilled readers showed sensitivity to cohesion (greater activation and synchronization when clause connectives were present than when they were not). These finding support the hypothesis that skilled reading comprehension requires recruitment of the RH on an “as needed” basis. We describe the dynamic spillover hypothesis, a new theoretical framework that outlines the conditions under which RH language contributions are most likely evoked.